ANALYSIS OF THE SYSTEM ROBUST PROCESS (SRP) IMPLEMENTATION TOWARDS ACCELERATION OF RECEIVABLES COLLECTION AT PT UNITED TRACTORS, Tbk - Arsyadanal Haq Imanda; Keulana Erwin; Isfenti Sadalia (RADJA PUBLIKA, 2025)
Analysis of Implementing the System Robust Process (SRP) on Accelerating Receivables Collection at PT United Tractors, Tbk. This research analyzes applying the robust process (SRP) system to accelerate receivables collection at PT United Tractors, Tbk. Medan Branch Office. This type of research is quantitative descriptive research. This type of research is quantitative descriptive research. The population in this research is PT Receivables reports. United Tractors Tbk Medan Branch Office. This study's sample of receivables data is PT United Tractors Tbk Medan Branch Office period 2019-2024. The data collection techniques used were interviews, documentation, and literature study. The analysis was carried out using descriptive methods. This data was analyzed using ratio analysis, especially those related to the receivables turnover rate, collection period, delinquency ratio, and collection ratio. The research results show that the implementation of the System Robust Process (SRP) can have a positive impact on accelerating the collection of receivables. It can be concluded that the turnover of receivables at PT United Tractors Tbk is quite good and running effectively. Implementing the System Robust Process (SRP) affects the average collection of receivables. Since the implementation of SRP at PT United Tractors Tbk, the average collection of receivables has experienced a decrease in the maturity of receivables compared to the year before the implementation of SRP. After implementing the System Robust Process (SRP), the delinquency ratio experienced a very significant decrease in 2021. The delinquency ratio was 1%, while in 2022-2024, the delinquency ratio was 12%, compared to before the implementation of the System Robust Process (SRP), which was 23%. The collection ratio after implementing the System Robust Process (SRP) experienced a very significant increase in 2021, the collection ratio was 99%, while in 2022-2024, the collection ratio was 98%, compared to before the implementation of the System Robust Process (SRP), namely in 2019 it was 78%.